ANÁLISIS DE LA ACTIVIDAD APÍCOLA COMO DESARROLLO SOCIOECONÓMICO EN LAS FAMILIAS DEL CANTÓN EL EMPALME: ESTUDIO DE CASO - Giler Cobeña, Emely Elizabeth (2023)
This investigation was carried out in the El Porvenir facility located in the El Empalme canton, Guayas province, the objective of the present investigation was to determine the analysis of the beekeeping activity as socioeconomic development in families of the El Empalme canton, The present investigation was based on a case study on the description and analysis of a beekeeper through a dynamic survey, where the continuous collection of economic and social data of interest to the same case was carried out.